Fatal Rift Valley Fever Outbreak Caused By Exposure To Meat FromSick And Dead Livestock: Uganda, July 2018 - Mirembe, Bernadette B; Ario, Alex R.; Birungi, Doreen; Bulage, Lilian; Kisaakye, Esther; Kwesiga, Benon; Kabwama, Steven N.; Muwanguzi, David; Kadobera, Daniel; Balinandi, Steven; Birungi, Deo N. (Research Square, 2021)
Page2/12AbstractBackground: Rift Valley Fever (RVF) is a viral hemorrhagic fever that can be fatal to humans and livestock. During June-October 2018,reported RVF cases increased sharply in eight western and central Ugandan districts. We investigated to identify the scope of theoutbreak, determine risk factors, and recommend control measures.Methods: We de
Keywords: Rift Valley Fever; Outbreak; One Health; Global Health Security; Uganda